2020
DOI: 10.1038/s41598-020-77275-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 predictability in the United States using Google Trends time series

Abstract: During the unprecedented situation that all countries around the globe are facing due to the Coronavirus disease 2019 (COVID-19) pandemic, which has also had severe socioeconomic consequences, it is imperative to explore novel approaches to monitoring and forecasting regional outbreaks as they happen or even before they do so. To that end, in this paper, the role of Google query data in the predictability of COVID-19 in the United States at both national and state level is presented. As a preliminary investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
95
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 51 publications
6
95
0
3
Order By: Relevance
“…Numerous studies have shown how analysing web search queries can assist in describing and predicting outbreaks especially in the context of sparse data 19 21 . This approach has also been used for COVID-19 already 22 , 23 . However, web searches have also been analysed to describe public attention in relation to a public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown how analysing web search queries can assist in describing and predicting outbreaks especially in the context of sparse data 19 21 . This approach has also been used for COVID-19 already 22 , 23 . However, web searches have also been analysed to describe public attention in relation to a public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common approaches to tracking COVID-19 dynamics is through regular snapshots in the form of choropleth maps, or where the number of cases are mapped by administrative units such as states or counties 2 . One may gain a sense of dynamics - change over time - by manually toggling back and forth through the maps or by developing a change map, where rates or differences are calculated on a per-region basis between two snapshots 3 , 4 . While such mapping is integral to understanding and responding to the pandemic, there remains a subjective element when the viewer flips back and forth between maps or must interpret change between two fixed dates among many.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, scientists are increasingly adopting infoveillance tools to monitoring the infodemic on websites, social media, and newspapers [5]. In particular, Google Trends-an open online infoveillance tool developed by Google TM -has been widely used by the scientific community not only as for quantifying disinformation but also to make epidemiological predictions on the spread of infectious diseases, including COVID-19 [6][7][8][9]. This type of study is based on the search for statistical cross-correlations between users' web searches related to specific diseases, such as symptoms, drugs, therapies, vaccines, number of infected people, number of deaths, etc., and the number of disease contagions and deaths officially registered after a certain timespan.…”
Section: Introductionmentioning
confidence: 99%